Protective factors for teen mothers: relations among social support, psychological resources, and child rearing practices - VanDenBerg, Maggie P., author; MacPhee, David, advisor; Youngblade, Lise, committee member; Aloise-Young, Patricia, committee member (Colorado State University. Libraries, 2012)
Teen mothers face increased challenges when rearing children, largely influenced by development as an adolescent and the support networks they have available to them. Based on two theories of parental and adolescent development, measures of well-being including self-efficacy, depression, and future orientation are mechanisms that can be altered by support networks, and function as protective factors for functional parenting. This study of 344 teen mothers tests the hypotheses that teen mothers who have more supportive primary social networks have greater confidence in parenting abilities, less propensity towards depression, and a more optimistic sense of the future. Results indicate that relations of support functions (intimacy and support satisfaction) and nurturant child rearing practices are partially mediated by self-efficacy and fully mediated by depression. These findings emphasize the importance of supportive characteristics in support networks for teen mothers and parental well-being, both of which may foster the development of non-coercive parenting.
Keywords: adolescent development; teen mothers; resilience; parenting